PENGARUH KUALITAS PELAYANAN DAN WORD OF MOUTH TERHADAP KEPUTUSAN PENGAMBILAN KREDIT PADA KSP. LEMBING SEJAHTERA MANDIRI - Ni Wayan Ari, Sudiartini; Ni Wayan, Ardani.; Gede Agus, Subawa (PIRAMIDA; Vol 14 No 2 (2018): PIRAMIDA`- Jurnal Kependudukan dan Pengembangan Sumber Daya Manusia, 2019)
Quality of service is one of the company's assets in an effort to meet the needs and desires and will ultimately create customer satisfaction and a positive Word Of Mouth. The purpose of this study is to determine how much the influence of service quality and Word Of Mouth  to credit decision at  KSP. Lembing Sejahtera Mandiri either partially or simultaneously. The type of research used is explanatory or descriptive research with quantitative approach. This research uses multiple linear regression analysis.               The population of this study are clients who are members of KSP. Lembing Sejahtera Mandiri with a total sample of 70 respondents. The results of this study indicate that service quality and Word Of Mouth have positive and significant influence either partially or simultaneously.                This research is expected to provide benefits to the cooperative to improve the quality of service to produce Word Of Mouth positive at KSP. Lembing Sejahtera Mandiri is related to customer decision in credit taking.